2023
DOI: 10.3389/fcvm.2023.1205475
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive heart disease: risk factors, complications and mechanisms

Abstract: Hypertensive heart disease constitutes functional and structural dysfunction and pathogenesis occurring primarily in the left ventricle, the left atrium and the coronary arteries due to chronic uncontrolled hypertension. Hypertensive heart disease is underreported and the mechanisms underlying its correlates and complications are not well elaborated. In this review, we summarize the current understanding of hypertensive heart disease, we discuss in detail the mechanisms associated with development and complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 249 publications
(288 reference statements)
0
14
0
Order By: Relevance
“…23,24 This can lead to complications of hypertension such as cardiovascular diseases or stroke without notice. 25,26 The finding in this study showed most hypertensive patients had duration of hypertension of less than 5 years with controlled blood pressure. This supports a previous study by Siti (2018), which reported that patients experiencing hypertension for less than 5 years had better compliance in controlling blood pressure levels than those experiencing hypertension for more than 5 years.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…23,24 This can lead to complications of hypertension such as cardiovascular diseases or stroke without notice. 25,26 The finding in this study showed most hypertensive patients had duration of hypertension of less than 5 years with controlled blood pressure. This supports a previous study by Siti (2018), which reported that patients experiencing hypertension for less than 5 years had better compliance in controlling blood pressure levels than those experiencing hypertension for more than 5 years.…”
Section: Discussionmentioning
confidence: 54%
“…Monitoring the patient's quality of life is needed to determine the right therapy according to the patient's clinical condition to achieve the therapeutic goal of improving quality of life. 24,25 In addition to quality of life, direct medical costs should impact the quality of life. 10 Direct medical costs are directly related to hypertensive treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial hypertension is the principal risk factor for cardiovascular diseases [1] resulting in target organ damage, including heart, kidney, and brain damage. Hypertensive heart disease, due to chronic pressure overload, is characterized by structural remodeling of the LV in terms of hypertrophic growth and fibrosis, which are associated with a worsening of diastolic and systolic function, alterations in energetic metabolism, and electrical abnormalities [2]. Although initial mass enlargement aims to normalize LV wall stress under conditions of higher hemodynamic load while maintaining adequate performance, thus representing a compensatory reaction, maladaptive growth of the hypertensive heart in later periods is associated with worse prognosis and frequently results in the development of overt heart failure (HF).…”
Section: Introductionmentioning
confidence: 99%
“…When angiotensin II binds to its receptors, such as AGTR1, it activates molecular pathways such as inflammation, vasoconstriction, oxidative stress, and sodium and water reabsorption, resulting in high blood pressure and hypertension. 12 …”
Section: Introductionmentioning
confidence: 99%
“…When angiotensin II binds to its receptors, such as AGTR1, it activates molecular pathways such as inflammation, vasoconstriction, oxidative stress, and sodium and water reabsorption, resulting in high blood pressure and hypertension. 12 A case-control study found that individuals with the CC genotype of AGTR1 rs5186 were at a 2.4 times higher risk of developing essential hypertension than individuals with AC and AA genotypes, suggesting that AGTR1 upregulation plays an important role in essential hypertension. 13 A previous study on peripheral arterial diseases patients investigating the effects of both of these RAS-related gene variants (AGT rs699 and AGTR1 rs5186), as well as ACE rs1799752 and angiotensin II receptor type 2 (AGTR2) rs35474657, found that carriers of variant genotypes had significantly higher levels of HDL-C, LDL-C and triglycerides (TG) than patients without these SNPs.…”
Section: Introductionmentioning
confidence: 99%